PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 125 PEKANBARU - Yuli Gustavia; Hendri Marhadi; Lazim Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is the low learning outcomes Social Sciences student, with an average grade 67.1. Based on the problems appear researchers conducted a study entitled